“Imaging the Image of God”: David H. Kelsey oor die Imago Dei - Marais, Nadia (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The doctrine of the imago Dei has long functioned as a core theological affirmation in theological anthropologies. However, interpretations of what it means for human beings to be created in the image of God vary widely, which, in turn, has implications for the discourses on human uniqueness, human dignity, human rights and ecological sustainability, among others. This article traces four normative interpretations of the imago Dei – substantive, functional, relational and eschatological – and goes on to argue that these four interpretations need not be understood as mutually exclusive, as they are often treated, but could, within an unsystematic systematic whole, be held together. This article analyses David Kelsey’s understanding of the imago Dei within his recently published theological anthropology, Eccentric Existence (2009), to illustrate how these four interpretations could function together.